Plaque assay of Sendai virus in monolayers of a clonal line of porcine kidney cells. - Ito, H (1976)
The MN strain of Sendai virus formed distinct plaques in monolayers of PS-Y15 cells, an established porcine kidney cell line. The plaque-forming ability was neutralized by specific antibody to the virus. A linear relationship was found between the concentration of virus and the number of plaques. The sensitivity of this assay was about equal to that of the in ovo titration. When applied to the serum neutralization test, the end points obtained were comparable to those of the hemagglutination-inhibition and complement-fixation tests.